Design and development of a locomotive assisted probe distal end for intra cavity imaging - Vinay, Ravi (2009)
Automated inspection of inaccessible areas is still a challenging process in today's world. Accessing such areas often requires a deployment of a microinspection device which can easily maneuver through the cavities and surfaces. It is also required to map and reconstruct the profiles of these cavities and surfaces in order to study the changes happening in the profile. Cavity inspection and the studies based on the changes in cavity profiles are important for understanding the defects and changes happening within cavities like crack, protrusion etc.